Barrier effect and cross-border cooperation. The Sweden-Norway INTERREG-A territorial effects - Medeiros,Eduardo (2014)
Historic developments that occurred in the last centuries have affected the barrier effect of national borders in Europe and, consequently, the degree and the intensity of the cooperation between neighbouring countries. However, the establishment of the European single Market, in the last three decades, has deepened the cross-border cooperation inside the EU territory. in this respect, the INTERREG-A initiative has played a major role, since 1990. This article intends to shed some light on the progress of the cross-border cooperation in the Swedish-Norwegian border region, and the territorial effects of the INTERREG-A programme in the reduction of the barrier effect along the border in five dimensions (institutional-urban, accessibility, culture-social, environmental-heritage and economy-technology).